Impact evaluation of a conditional cash transfer program: the Nicaraguan Red de Protección Social - Maluccio, John A.; Flores, Rafael (International Food Policy Research Institute, 2004)
This paper presents the main findings of a quantitative evaluation of the Red de Protección Social (RPS), a conditional cash transfer program in Nicaragua, against its primary objectives. These included supplementing income to increase household expenditures on food, reducing primary school desertion, and improving the health care and nutritional status of children under age 5. The evaluation design is based on a randomized, community-based intervention with measurements before and after the intervention in both treatment and control communities. Where possible, we erred on the side of assessing effects in conservative manners, for example, in the calculation of standard errors and the treatment of possible control group contamination. Overall, we find that RPS had positive (or favorable) and significant double-difference estimated average effects on a broad range of indicators and outcomes. Where it did not, it was often due to similar, smaller improvements in the control group that appear to have been stimulated indirectly by the program. Most of the estimated effects were larger for the extreme poor. The findings presented here played an important role in the decision to continue this effective program." -- Authors' Abstract